Diagnostic Performance of the Global Leadership Initiative on Malnutrition (GLIM) compared with Malnutrition Nutritional Assessment (MNA) in Assessing Malnutrition among Geriatric Inpatients - Astrine Permata Leoni; Wita Rizki Amelia; Purwita Wijaya Laksmi; Ahmad Syauqy (Jurnal Penyakit Dalam Indonesia)
Introduction. As many as 76.6% of patients aged 60 years and above (elderly) are malnourished or at risk of malnutrition based on MNA within the first 48 hours of hospital admission. The prevalence of malnutrition varies widely depending on the population studied, the healthcare setting and the tools used for the assessment. To date, SGA is widely used in the diagnosis of malnutrition for adults and MNA for elderly patients. Recently, experts proposed empirical consensus of GLIM criteria for determining the diagnosis of malnutrition in adults. This study aimed to investigate the diagnostic performance of GLIM criteria as a new consensus in determining the diagnosis of malnutrition in comparison to MNA as a semi-gold standard for nutritional assessment in the elderly.